Visual Depictions of Our Evolutionary Past: A Broad Case Study Concerning the Need for Quantitative Methods of Soft Tissue Reconstruction and Art-Science Collaborations - Campbell, Ryan M.; Vinas, Gabriel; Henneberg, Maciej; Diogo, Rui (Frontiers in Ecology and Evolution, 2021)
Flip through scientific textbooks illustrating ideas about human evolution or visit any number of museums of natural history and you will notice an abundance of reconstructions attempting to depict the appearance of ancient hominins. Spend some time comparing reconstructions of the same specimen and notice an obvious fact: hominin reconstructions vary in appearance considerably. In this review, we summarize existing methods of reconstruction to analyze this variability. It is argued that variability between hominin reconstructions is likely the result of unreliable reconstruction methods and misinterpretation of available evidence. We also discuss the risk of disseminating erroneous ideas about human evolution through the use of unscientific reconstructions in museums and publications. The role an artist plays is also analyzed and criticized given how the aforementioned reconstructions have become readily accepted to line the halls of even the most trusted institutions. In conclusion, improved reconstruction methods hold promise for the prediction of hominin soft tissues, as well as for disseminating current scientific understandings of human evolution in the future.